Manipulation of peptide-fatty acid bioconjugates on graphene: effects of fatty acid chain length and attachment point. Issue 31 (27th July 2022) - Perdomo, Yuliana; Jin, Ruitao; Parab, Atul D.; Knecht, Marc R.; Walsh, Tiffany R.
Abstract : We demonstrate that attachment of fatty acids to graphene-binding peptides modulate interfacial interactions and structures, for enhancing sensing device applicability. Abstract : The non-destructive functionalisation of graphene in aqueous media is a critical process with the potential to enhance the versatility of the 2D nanosheet material as a technological enabler. This could also unlock strategies for a wider uptake of graphene in bio-related applications. Graphene functionalisation can be achieved using peptides that specifically recognise the carbon-based material, resulting in persistent non-covalent adsorption without damaging the nanosheet. Bio-conjugation of non-natural moieties with these peptides can incorporate multifunctionality, further extending the applicability of these interfaces. Here, bio-conjugates comprising a graphene-binding peptide with a fatty acid chain of varying length are investigated for their binding affinity and adsorbed structures at the aqueous graphene interface. Through an integration of quartz crystal microbalance and atomic force microscopy data with advanced sampling molecular simulations, variations in the binding of these bio-conjugates is determined. Conjugation at either terminus led to good interfacial contact, and for a given attachment point, the changes in the fatty acid length did not substantially disrupt the conformations of the adsorbed peptide domain. These findings provide a solid foundation for designing multi-functional bio-interfaces for sensing and healthcare.